The Economic Burden of Dementia: Evidence from a Survey of Households of People with Dementia and Their Caregivers - Oba, Hikaru (Int J Environ Res Public Health, 2021)
Although a cognitive impairment such as dementia causes serious economic problems among older people, its impact on economic activities is unclear. This study investigated the actual conditions of economic activities and the current status of the financial support systems among people with dementia and caregivers. One hundred and five dyads participated in the survey. Each dyad consisted of an older person with Alzheimer’s disease and their caregiver. The Mini-Mental State Examination (MMSE) and Functional Assessment Staging (FAST) were used to evaluate the cognitive functions of people with dementia. The caregivers were asked questions concerning the financial status of the household and their utilization of the financial support systems available to people with dementia. Average monthly care costs significantly increased according to the severity of dementia, while household income and spending incurred no significant changes. People with dementia experienced financial problems (including a large amount of erroneously purchased, unnecessary shopping), even though their assets were informally managed by their caregivers. Financial support systems such as adult guardianship and civil trust systems were rarely known and used. We proposed the propagation of the adult guardianship and civil trust systems and the development of contract guidelines for elderly customers including people with dementia.